History and Cultural Memory in Neo-Victorian Fiction - Mitchell, Kate. author. aut Link
IX, 222 p. 1 illus.
Keywords: A PDF version of this book is available for free in open access via the OAPEN Library platform, www.oapen.org. Arguing that neo-Victorian fiction enacts and celebrates cultural memory, this book uses memory discourse to position these novels as dynamic participants in the contemporary historical imaginary.